-5(v+1)=-4(2v-1)+9v

Simple and best practice solution for -5(v+1)=-4(2v-1)+9v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(v+1)=-4(2v-1)+9v equation:


Simplifying
-5(v + 1) = -4(2v + -1) + 9v

Reorder the terms:
-5(1 + v) = -4(2v + -1) + 9v
(1 * -5 + v * -5) = -4(2v + -1) + 9v
(-5 + -5v) = -4(2v + -1) + 9v

Reorder the terms:
-5 + -5v = -4(-1 + 2v) + 9v
-5 + -5v = (-1 * -4 + 2v * -4) + 9v
-5 + -5v = (4 + -8v) + 9v

Combine like terms: -8v + 9v = 1v
-5 + -5v = 4 + 1v

Solving
-5 + -5v = 4 + 1v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-1v' to each side of the equation.
-5 + -5v + -1v = 4 + 1v + -1v

Combine like terms: -5v + -1v = -6v
-5 + -6v = 4 + 1v + -1v

Combine like terms: 1v + -1v = 0
-5 + -6v = 4 + 0
-5 + -6v = 4

Add '5' to each side of the equation.
-5 + 5 + -6v = 4 + 5

Combine like terms: -5 + 5 = 0
0 + -6v = 4 + 5
-6v = 4 + 5

Combine like terms: 4 + 5 = 9
-6v = 9

Divide each side by '-6'.
v = -1.5

Simplifying
v = -1.5

See similar equations:

| 23=y/5+12 | | 2x-14=26 | | 15-4x=3 | | 4x+7y=209 | | 65*65-81*x*x=16*16*x*x | | 5y=-10/9 | | 5(y-5)-1=-2(-2y+6)-7y | | 14=-7/5u | | -2(2v-3)+7v=9+3(5v-2) | | 65*65-81*x*x=36*x*x | | -4/3w=24 | | 12-5/8 | | 3(-x+4)+6=-6x+3 | | 4/x-2=(-4/x+2)+(24/(x-2)(x+2)) | | 14m=400.40 | | 2n+7=5x | | 3v=3.75 | | 2(3x-5)=.5 | | 31.25=x/5 | | -2(x+2)=2x-1+5(2x+1) | | (7-x)(10-x)=(7)(10-1.5x) | | 6/10x=60 | | w/12.8=4 | | .40x+.15(140-x)=.19(140) | | -2(v+9)=7v+45 | | 6i+10y=-13 | | 2x-13=-7(x+7) | | 8x+4=-6+7x | | 3v=9/2 | | .25x+.15(140-x)=.19(140) | | y/4+3.2+5.2 | | 3v+6(v+2)=21 |

Equations solver categories